2023
DOI: 10.1101/2023.10.16.558465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastrulation-stage gene expression inNipbl+/-mouse embryos foreshadows the development of syndromic birth defects

Stephenson Chea,
Jesse Kreger,
Martha E. Lopez-Burks
et al.

Abstract: In animal models, Nipbl-deficiency phenocopies gene expression changes and birth defects seen in Cornelia de Lange Syndrome (CdLS), the most common cause of which is Nipbl-haploinsufficiency. Previous studies in Nipbl+/- mice identified aberrant gene expression and heart defects as early as cardiac crescent (CC) stage. Here, we performed single-cell RNA-sequencing on wildtype (WT) and Nipbl+/- mouse embryos at CC- and earlier (gastrulation) stages. Nipbl+/- embryos had fewer mesoderm cells than WT and altered … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 186 publications
(321 reference statements)
0
1
0
Order By: Relevance
“…It is possible that some of the molecular basis for developmental abnormalities is shared between NIPBL deficiency and STAG2 mutation. A study describing single cell RNA sequencing of early-stage mouse embryos with one deleted copy of Nipbl showed that these embryos also experience changes in mesoderm fate and have altered mesoderm cell populations (Chea et al, 2024). Nipbl loss altered the regulation of genes involved in EMT, which parallels our findings in stag2b mutant zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some of the molecular basis for developmental abnormalities is shared between NIPBL deficiency and STAG2 mutation. A study describing single cell RNA sequencing of early-stage mouse embryos with one deleted copy of Nipbl showed that these embryos also experience changes in mesoderm fate and have altered mesoderm cell populations (Chea et al, 2024). Nipbl loss altered the regulation of genes involved in EMT, which parallels our findings in stag2b mutant zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%